S42 Transbronchial cryobiopsies in the diagnosis of Interstitial Lung Diseases- first UK experience. (12th November 2015) - Mikolasch, TA; Borg, E; Thakrar, R; Holmes, V; Booth, HL; Porter, JC; Navani, N
Abstract : Introduction: Despite radiological advancements histology is often needed in the diagnosis of Interstitial Lung Disease (ILD). In order to obtain lung biopsies of adequate size and quality patients traditionally undergo a surgical lung biopsy associated with a mean hospital stay of 3.5 days and a complication rate of up to 28%. 1 We are the first UK centre to have set up a minimally invasive, day case transbronchial cryobiopsy service in the diagnosis of ILDs. Aims: To establish a transbronchial cryobiopsy service for ILDs and assess complication rates and diagnostic yield. Methods: Patients were selected following discussion at the Interstitial Lung Disease Multidisciplinary Team meeting. Only patients in whom significant diagnostic doubt remained after thorough clinic-radiological work up were considered. All procedures were performed with the patient self-ventilating under deep sedation with propofol using a flexible bronchoscope and 2.4 mm cryoprobe (ERBE). All but one procedure was performed under fluoroscopy guidance. All but the first two cases were performed following intubation with an uncuffed ET tube (Bronchoflex, Rusch). We introduced prophylactic IV tranexamic acid 1 g as premedication and endobronchial adrenaline routinely as part of our protocol after the first 5 cases. 1–5 samples were taken per procedure from several sub-segments of one lobe pre-selected by CT imaging. Results: 14 procedures were carried out on 13 patients. 9 patients were male. Mean age 63, mean predicted TLCO 50%; mean number of biopsies 2.7; mean aggregate biopsy size 624 mm 3 . Complications: 2 pneumothoraces requiring chest drain insertion; 1 case of moderate bleeding and 1 case of severe bleeding managed with endobronchial adrenaline and suction only. All cases were performed as outpatient day cases with patients discharged home 2– 4 h after the procedure except the 2 patients requiring chest drains. Conclusions: Our transbronchial cryobiopsy service is comparable in complication rates and diagnostic yield with larger case series from established centres outside the UK. Transbronchial cryobiopsy provides potential for minimally-invasive acquisition of sizeable lung biopsies. Further research is needed to establish whether transbronchial cryobiopsy should replace surgical lung biopsy in selected cases. Reference: 1 Morris D, Zamvar V. The efficacy of video-assisted thoracoscopic surgery lung biopsies in patients with interstitial lung disease: a retrospective study of 66 patients. J Cardiothorac Surg . 2014;9 :45